2021
DOI: 10.1186/s13568-021-01184-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality improvement of soybean meal by Bacillus velezensis and Lactobacillus plantarum during two-stage solid- state fermentation

Abstract: Bacillus velezensis is widely used for agricultural biocontrol, due to its ability to enhance plant growth while suppressing the growth of microbial pathogens. However, there are few reports on its application in fermented feed. Here, a two-stage solid-state fermentation process using Bacillus velezensis followed by Lactobacillus plantarum was developed to degrade antinutritional factors (ANFs) and improve soybean meal (SBM) nutrition for animal feed. The process was evaluated for performance in degrading SBM … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…Compared to the other two treatments, SSF is widely used because of its environmental protection, large-scale production and high degradation rate [ 3 ]. However, a number of issues regarding SBM fermentation, such as the microbial flora that are responsible for the quality of fermentation during fermentation, were only reported by Chen et al [ 4 ] and Wang et al [ 5 ], not to mention what happens after fermentation, and the effect of fermentation on toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the other two treatments, SSF is widely used because of its environmental protection, large-scale production and high degradation rate [ 3 ]. However, a number of issues regarding SBM fermentation, such as the microbial flora that are responsible for the quality of fermentation during fermentation, were only reported by Chen et al [ 4 ] and Wang et al [ 5 ], not to mention what happens after fermentation, and the effect of fermentation on toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic SSF (ASSF) is a common method used in SBM fermentation ( 19 , 20 ). The two-stage (first stage, aerobic fermentation; second stage, anaerobic fermentation) SSF process with different microorganisms has also been studied in recent years ( 21 , 22 ). Anaerobic SSF has unique advantages in water and energy savings, decreased weight loss of material, and environmental protection; it will be the future direction of the fermentation industry ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The attention of researchers in East and Southeast Asia studying the technological and dietological experience of obtaining traditional food products through the fermentation of soybeans using Aspergillus and Rhizopus mushrooms has significantly enriched biotechnology worldwide [214]. It was found that in the process of solid-phase fermentation, not only did the protein concentration and the nutritional value increase, the content of anti-nutritional factors of the substrate decreased [205,[222][223][224]. The biosynthesis of active substances is also more efficient [225], including antibiotics [226,227], phytohormones, food pigments, and alkaloids.…”
Section: Fermentation Methods For the Production Of Probiotics 721 Solid-state Fermentationmentioning
confidence: 99%
“…Although such media provide well-reproducible and homogeneous spore preparations, they are relatively expensive and provide a relatively low spore yield (1 × 10 8 -1 × 10 10 CFU/mL). The concentration of the carbon source can play a decisive role in the process of sporogenesis by individual bacilli because it has been shown that with an increase in glucose concentration, the concentration of vegetative cells increases, but initial glucose concentrations above 5 g/L inhibit sporulation and sporulation efficiency decreases [191,193,[200][201][202][203][204][205][206][207][208][209][210][211]. It has been suggested that depletion of the carbon source is the main stimulus for sporulation by Bacillus spp.…”
Section: Cultivation Conditions For Bacillus Spp Growth and Spore Productionmentioning
confidence: 99%
See 1 more Smart Citation